THE INFLUENCE OF THE ELECTROCHEMICAL TREATMENT ON CU-AL-AG ALLOYS IN DEAERATED 0.5M NAOH - Cabot, P. L.; Centellas, F. A.; Garrido, J. A.; Sumodjo, PTA; Benedetti, Assis Vicente [UNESP]; Nakazato, R. Z. (Chapman Hall Ltd, 1991)
The effect of consecutive cyclic polarization in de-aerated 0.5 M NaOH solutions on the surface microstructure of mechanically polished Cu-Al-Ag alloys of different compositions and heat treatments has been studied using optical microscopy, SEM and EDS. The current peaks of the cyclic polarization curves do not depend on the alloy composition in the composition range studied. The repetitive potential scans between H2 and O2 evolution in alkaline media lead to preferential dissolution of aluminium, the roughness and phase composition of the surface of the alloys changing significantly. The quasistationary I-E curves of the different Cu-Al-Ag alloys studied consist in the superposition of the quasistationary I-E curves of high-purity Cu and Ag, the EDS microanalysis showing that aluminium is not present on the surface of the alloy in these conditions.